OPTIMALISASI KESADARAN GENDER DALAM BERMEDIA - Ashaf, Abdul Firman (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2025)
The main objective of this service activity is to contribute to adolescent literacy in daily media activities, especially in terms of gender awareness in media. The main aspect contributed by this activity is the existence of cognitive changes, especially in gender awareness. These changes are related to increasing knowledge regarding gender aspects in values and activities in relations between men and women as well as providing changes in media awareness, especially in terms of gender literacy in mass and digital media